Growth and yield pattern of microgreen under different types of artificial lighting - Putri, Envry Artanti Duidahayu; Fajri, Hauzan Ariq Musyaffa; Iswari, Firstina; Muhammad, Fadlan Atalla; Fauziah, Rossita; Budiarto, Rahmat (Universitas Padjadjaran, 2023)
Microgreen is a popular food product that is interesting to study and can be produced in the building with the support of artificial light, especially in terms of smart lights. This study aims to analyze the growth and yield response of red amaranth, red radish, and coriander microgreens under different types of light color treatment from smart lights. The study was conducted in August 2022 at the microgreen culture room, Department of Agronomy, Universitas Padjadjaran, Indonesia, using a completely randomized design with two factors, namely three levels of plant species and five levels of smart light color. The results showed differences in seed viability, first-day count, and the day the cotyledons were open among three microgreen species. Seed growth into microgreens had the same pattern, namely linear and positive, even in the light absence condition as the evidence of etiolation occurrence leading to the production of thin and yellow pale color of microgreens. The difference in light color is specific to each type of plant. Red radishes thrived in all colors, although red light tended to do better. On the other hand, red amaranth was inhibited in red light and coriander in white light. Blue light is strongly recommended for increasing red amaranth and coriander microgreens yields.